Preparation method of composite flocculant based on efficient water treatment
By preparing modified liquid and acid leaching liquid, and combining citric acid complexing liquid and modified starch, a spatial network structure with Fe3+ as a bridge is constructed, which solves the problem of insufficient flocculation performance of existing composite flocculants in complex water environments, and achieves efficient flocculation and sedimentation effects, making it suitable for the treatment of wastewater with high turbidity and complexity.
Patent Information
- Application Number
- CN202511335686.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-12-19
AI Technical Summary
Existing composite flocculants have insufficient flocculation and sedimentation performance in complex aquatic environments. They also suffer from insufficient modification depth and uneven distribution of functional groups, resulting in loose floc structure and slow sedimentation speed, making it difficult to meet the treatment requirements of high turbidity and complex wastewater.
By preparing modified liquid and acid leaching liquid, a polymer is formed by free radical polymerization under a nitrogen atmosphere. Combined with citric acid complexing liquid and modified starch, a spatial network structure with Fe3+ as a bridge is constructed to form a stable organic-inorganic composite network system, thereby enhancing the flocculation and sedimentation performance of the flocculant.
It improves the flocculation efficiency and sedimentation speed of flocculants, enhances the removal rate of heavy metals and dyes, and improves the structural compactness and sedimentation performance of flocculants, making it suitable for the treatment of wastewater with high turbidity and complexity.
Smart Images

Figure BDA0005602380270000171
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of flocculant processing, in particular to a preparation method of a composite flocculant based on efficient water treatment. BACKGROUND
[0002] In recent years, with the increasing demand for industrial wastewater and domestic sewage treatment, flocculants are increasingly widely used in water treatment processes. In water treatment technology, flocculants are the core materials for efficiently removing suspended particles, colloids, organic matter and heavy metal ions in water. The technical performance directly determines the treatment efficiency and cost.
[0003] At present, composite flocculants are widely used in municipal sewage, dyeing wastewater, heavy metal contaminated water and other fields due to their combined organic macromolecular long-chain adsorption bridging ability and inorganic component charge neutralization and sedimentation coagulation. Common composite flocculant materials include polyacrylamide (PAM) macromolecules, natural starch, chitosan, inorganic salts and mineral modified materials. In order to improve the comprehensive performance of composite flocculants, common modification methods include cationic modification, graft polymerization, amidation and physical and chemical treatment methods such as thermal activation and acid pickling, so that organic and inorganic components can effectively cooperate in structure, improve flocculation efficiency and sedimentation speed.
[0004] Although the material system and modification method in the prior art have made certain progress in improving flocculation efficiency, there are still some deficiencies in complex water environment. Some flocculant modification methods only stay at the physical mixing level, resulting in insufficient modification depth, uneven distribution of functional groups, and inability to fully play the synergistic effect of each component, forming a structure network with poor synergistic effect. The root cause of these problems is that there is a lack of effective interface reaction mechanism between organic and inorganic phases, the complexation reaction in the compounding process is insufficient, the functional group design lacks pertinence, and the intermolecular force is weak, resulting in loose flocculation structure and slow sedimentation speed, which is difficult to meet the treatment needs of high turbidity and high complexity wastewater.
[0005] In view of the technical defects in this regard, a solution is proposed. SUMMARY
[0006] The purpose of the present application is to provide a preparation method of a composite flocculant based on efficient water treatment, which solves the technical problem that the flocculation performance and sedimentation performance of the flocculant in the prior art need to be further improved.
[0007] The purpose of the present application can be achieved by the following technical solution: a preparation method of a composite flocculant based on efficient water treatment, comprising the following steps:
[0008] S1. Acrylamide, diallyl dimethyl ammonium chloride, 2-hydroxypropyl methacrylate and deionized water are placed in a reaction vessel and mixed evenly to obtain a mixed monomer.
[0009] S2. Place deionized water and sodium dodecyl sulfate in a reaction vessel under nitrogen atmosphere and stir. Slowly add the mixed monomers. Heat the reaction vessel to 55-65℃ and keep it at this temperature for 15-30 min. Add ammonium persulfate aqueous solution and keep it at this temperature for 4-6 h to obtain the modified solution.
[0010] The reaction principle for preparing the modified liquid is as follows:
[0011] In a nitrogen atmosphere, sodium dodecyl sulfate, an emulsifier, causes the mixed monomers to form uniform droplets in water. Ammonium persulfate decomposes into free radicals at 55-65°C, which initiates a free radical polymerization reaction of acrylamide, diallyl dimethyl ammonium chloride, and 2-hydroxypropyl methacrylate to obtain a modified liquid containing the polymer.
[0012] S3. Place the acid leaching solution in a reaction vessel and stir. Add the modified solution and modified starch, stir for 5-10 minutes, add the citric acid complex solution, heat the reaction vessel to 55-65℃, add sodium hydroxide aqueous solution to the system pH=6.5-7.0, keep the temperature for 15-30 minutes, and then process to obtain the composite flocculant.
[0013] The preparation reaction principle of composite flocculants is as follows:
[0014] During the reaction, Fe in the acid leaching solution 3+ / Al 3+ Metal complexes can coordinate with functional groups such as amide, hydroxyl, and carboxyl groups of polymers in the modified solution to form complexes. The Fe in the citric acid complexing solution... 3+ Complexes can also crosslink with polymer chains through hydrogen bonds, electrostatic interactions, or coordination bonds to construct Fe... 3+ The modified solution forms a spatial network structure for bridging. Simultaneously, the polymer and metal complex in the modified solution work synergistically through mechanisms such as physical adsorption, chemical complexation, and ion bridging to form a stable organic-inorganic composite network system. This system possesses triple flocculation functions, including polymer bridging, metal complexation sedimentation, and cation neutralization. Adjusting the system pH to 6.5-7.0 can stabilize Fe. 3+ The complexed state prevents hydrolysis and precipitation, ultimately yielding a composite flocculant.
[0015] Further, in step S1, the ratio of acrylamide, diallyl dimethyl ammonium chloride, 2-hydroxypropyl methacrylate, and deionized water is 4-6g:2-4g:1-2g:50-70mL; in step S2, the ratio of deionized water, sodium dodecyl sulfate, mixed monomers, and ammonium persulfate aqueous solution is 80-120mL:0.5-1g:80-100mL:2-4mL, and the concentration of the ammonium persulfate aqueous solution is 50wt%.
[0016] Further, in step S3, the ratio of the acid leaching solution, modified solution, modified starch and citric acid complex solution is 10-12 mL: 2-4 mL: 1-2 g: 10-12 mL, the concentration of the sodium hydroxide aqueous solution is 1-2 mol / L, and the post-treatment step includes: after the reaction is completed, the reaction system is allowed to cool to room temperature and stand for 10-12 h, the product is transferred to a rotary evaporator at a temperature of 90-100℃, and rotary evaporation is carried out under reduced pressure for 0.5-1 h. Undissolved matter is removed through an 80-mesh sieve to obtain the composite flocculant.
[0017] Furthermore, the acid leaching solution is prepared by the following steps:
[0018] A1. Place the volcanic rock powder in a muffle furnace, calcine it at high temperature, and grind it to obtain pretreated volcanic rock powder;
[0019] A2. Place the pretreated volcanic rock powder in a reactor, slowly add the mixed acid solution at 85-95℃, heat the reactor to 85-95℃, keep the reaction at this temperature for 1-2 hours, and then process it to obtain the acid leaching solution.
[0020] The reaction principle for preparing the acid leaching solution is as follows:
[0021] During the reaction, under high temperature, the acidity of oxalic acid increases, acting as a strong complexing agent to react with Fe in the pretreated volcanic rock powder. 3+ Al 3+ Ca 2+ and Mg 2+ The formation of stable soluble complexes by polyvalent metal ions enables selective extraction of surface-active metal components, generating an acid leaching solution rich in metal complexes. Simultaneously, the carboxyl groups in oxalic acid can undergo proton exchange with the hydroxyl groups in the aluminosilicate structure of pretreated volcanic rock powder, disrupting the interlayer structure of minerals and promoting the exfoliation and dissolution of amorphous components, ultimately yielding an acid leaching solution containing soluble complexes formed by polyvalent metal ions.
[0022] Furthermore, in step A2, the ratio of the pretreated volcanic rock powder to the mixed acid solution is 15-20g:150-200mL, and the mixed acid solution is composed of deionized water, hydrochloric acid, and oxalic acid in a ratio of 150-200mL:50-60mL:4-6g. The post-treatment step includes: after the reaction is completed, the reaction system is allowed to cool to room temperature, stand for 6-10 hours, and then separated into liquids. The supernatant obtained is the acid leaching solution.
[0023] Furthermore, the preparation method of the pretreated volcanic rock powder is as follows: volcanic rock powder is placed in a muffle furnace and heated to 300°C for the first time at a heating rate of 15°C / min. After holding the temperature for 15-25 min, it is heated to 500°C for the second time at a heating rate of 12°C / min. After holding the temperature for 35-45 min, it is heated to 700°C for the third time at a heating rate of 10°C / min. After holding the temperature for 40-60 min, it is naturally cooled to room temperature, ground, and passed through a 200-mesh sieve to obtain pretreated volcanic rock powder.
[0024] The reaction principle for preparing pretreated volcanic rock powder is as follows:
[0025] During the reaction, in the first heating stage, the high temperature of 300℃ removes free water and surface physically adsorbed water from the volcanic rock powder structure, achieving preliminary dehydroxylation, releasing hydroxyl groups and functional groups, activating the mineral surface, and releasing some organic impurities and gaseous components. In the second heating stage, the high temperature of 500℃ destroys the crystal structure of the volcanic rock powder, promotes the loosening of the mineral surface structure, and forms reactive defect sites. The metal oxides in it are transformed into an amorphous state. In the third heating stage, the high temperature of 700℃ further reorganizes the volcanic rock powder to form a stable framework, increasing the porosity of the product and obtaining pretreated volcanic rock powder.
[0026] Furthermore, the modified starch is prepared by the following steps:
[0027] B1. Place corn starch and deionized water in a reaction vessel, heat the reaction vessel to 80-90℃, keep the reaction at this temperature for 20-40 minutes, cool, and obtain gelatinized starch.
[0028] The reaction principle for preparing gelatinized starch is as follows:
[0029] During the reaction, when heated to 80-90℃, corn starch granules absorb water and swell, the molecular chains loosen, and the structure becomes amorphous. The straight and amylopectin chains gradually swell and partially dissolve, forming a uniform colloidal solution. After gelatinization, the hydroxyl groups on the starch surface are exposed, and gelatinized starch is finally obtained.
[0030] B2. Place the gelatinized starch in a reaction vessel and stir. Heat the reaction vessel to 45-55℃, add sodium hydroxide aqueous solution, keep warm and stir for 10-15 minutes, add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, heat the reaction vessel to 65-75℃, keep warm and react for 2-4 hours, and then process to obtain modified starch.
[0031] The reaction principle for the preparation of modified starch is as follows:
[0032] During the reaction, 3-chloro-2-hydroxypropyltrimethylammonium chloride undergoes intramolecular cyclization under alkaline conditions to generate an active intermediate of glycidyl quaternary ammonium salt. Furthermore, the epoxy group in 3-chloro-2-hydroxypropyltrimethylammonium chloride undergoes a nucleophilic ring-opening reaction with the hydroxyl group in the starch molecule to obtain modified starch with quaternary ammonium cation etherification modification.
[0033] Further, in step B1, the ratio of corn starch to deionized water is 5-10g:30-50mL; in step B2, the ratio of gelatinized starch, sodium hydroxide aqueous solution, and 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution is 5-10g:15-20mL:50-70mL, the concentration of sodium hydroxide aqueous solution is 2-3mol / L, and the concentration of 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution is 50-60wt%. The post-treatment steps include: after the reaction is completed, after the reaction system is cooled to a higher temperature, adding 1-2mol / L hydrochloric acid aqueous solution to adjust the pH of the system to 6.5-7, filtering, washing the filter cake with deionized water 2-4 times, transferring it to an oven at 50-60℃, drying to constant weight, grinding, and passing through a 200-mesh sieve to obtain modified starch.
[0034] Furthermore, the citric acid complex solution is prepared by the following steps:
[0035] C1. Place citric acid monohydrate and deionized water in a reaction vessel and stir. Add ferric nitrate nonahydrate and stir for 5-15 minutes. Add sodium acetate aqueous solution to adjust the pH of the system to 4-4.5. Heat the reaction vessel to 55-65℃ and keep the reaction at this temperature for 0.5-1 hour to obtain the precursor solution.
[0036] The reaction principle for preparing the precursor solution is as follows:
[0037] During the reaction, the three carboxyl groups and one hydroxyl group of the citric acid molecule can act as tetradentate polyligands to react with Fe in ferric nitrate nonahydrate. 3+ To form a stable complex, the pH of the system was adjusted to 4-4.5 using an aqueous sodium acetate solution to prevent Fe... 3+ Hydrolysis produces a precipitate. Simultaneously, this pH range favors the ionization of the three carboxyl groups in citric acid, promoting their reaction with Fe. 3+ The efficient complexation enhances the stability of the complex, ultimately yielding a stable precursor solution.
[0038] C2. Place the precursor solution in a reaction vessel and stir. Slowly add 2-hydroxyethylamine and add saturated ammonium bicarbonate aqueous solution to adjust the pH of the system to 5.5-6.0. Heat the reaction vessel to 45-55℃ and keep it at this temperature for 1-2 hours to obtain the citric acid complex solution.
[0039] The reaction principle for preparing citric acid complex solution is as follows:
[0040] During the reaction, 2-hydroxyethylamine contains both amino and hydroxyl groups. When added to the precursor solution, it can not only undergo amidation or esterification reactions with the remaining carboxyl groups in the citric acid to form covalent bonds, but also interact with Fe through hydrogen bonds / coordinate bonds. 3+ The formation of non-covalent bonds, and by controlling the pH to 5.5-6.0, facilitates the amidation or esterification reaction while maintaining Fe... 3+ The complexed state is maintained to prevent hydrolysis, ultimately yielding a citric acid complex solution.
[0041] Further, in step C1, the ratio of citric acid monohydrate, deionized water, and ferric nitrate nonahydrate is 15-20g:100-150mL:35-40g, and the concentration of the sodium acetate aqueous solution is 0.05-0.10mol / L; in step C2, the volume ratio of the precursor solution and 2-hydroxyethylamine is 120-150mL:6g.
[0042] The present invention has the following beneficial effects:
[0043] 1. This invention involves reacting citric acid monohydrate with ferric nitrate nonahydrate under mild acidic conditions to form Fe. 3+ A citric acid complex was subsequently introduced, followed by the introduction of 2-hydroxyethylamine to further participate in the complexation. By providing multiple coordination sites between the amino and hydroxyl groups, the stability and reactivity of the complex structure were enhanced. The addition of an ammonium bicarbonate buffer system and adjustment of the pH to 5.5-6.0 further promoted the formation of Fe... 3+ The complexation transformation results in a stable citric acid complex solution with carboxyl, hydroxyl, and amino groups. Citric acid, as a typical tricarboxylic acid, provides multiple complexation sites and can react with Fe in water. 3+ Pb 2+ Cu 2+ The formation of stable complexes by polyvalent metal ions enhances the flocculation and removal rate of heavy metals by the flocculant. Secondly, the residual Fe in the citric acid complex solution... 3+During alkaline adjustment, ions can further generate Fe(OH)3 colloids, which act as inorganic skeleton reinforcing agents, improving the compactness of the flocculant structure and sedimentation speed. At the same time, after the complexing liquid reacts synergistically with the acid leaching liquid, the modified liquid and the modified starch, a large number of functional groups such as carboxyl, hydroxyl and ammonium groups can be introduced into the composite flocculant system, improving the hydrophilicity and complexing flocculation performance of the flocculant.
[0044] 2. In this invention, the volcanic rock powder is first subjected to multi-stage heat treatment. This process helps to remove organic impurities, open the crystal lattice structure, and expose more active sites. Furthermore, the pretreated volcanic rock is acid-leached using a mixed acid solution composed of hydrochloric acid and oxalic acid, which effectively dissolves the Al content. 3+ Fe 3+ Ca 2+ and Mg 2+ The acid leaching solution contains active metal ions and colloidal structures containing silicon and aluminum. The metal cations and silicate fragments rich in the acid leaching solution can act as inorganic complexing points, forming a synergistic structural network with the organic polymers and modified starch in the subsequently added modified solution during the mixing reaction. The acid leaching solution is an inorganic reinforcing phase, which significantly improves the skeleton strength and spatial network construction ability of the composite flocculant, further enhancing the sedimentation and flocculation performance of the flocculant. Secondly, the polyvalent metal ions rich in the acid leaching solution have strong coordination ability. After adjusting the pH, they form metal hydroxide colloids, which can synergistically capture suspended particles, heavy metal ions, and silver ion dyes in wastewater with organic components, improving the sedimentation performance of flocs. In addition, the natural porous structure in volcanic rock retains a certain specific surface area and micropore channels after acid leaching, giving the flocculant good adsorption capacity.
[0045] 3. This invention also involves high-temperature hydrothermal treatment of corn starch to gelatinize it, destroying the original crystalline structure, exposing more hydroxyl functional groups, and enhancing hydrophilicity and reactivity. Subsequently, under alkaline conditions, 3-chloro-2-hydroxypropyltrimethylammonium chloride is introduced for etherification, introducing quaternary ammonium salt cationic groups, giving the starch a permanent positive charge, enhancing its electrostatic adsorption capacity for negatively charged dye pollutants and heavy metal complexes. The quaternary ammonium salt cationic groups provide charge neutralization sites, effectively neutralizing the negative charge on the surface of suspended particles in wastewater, promoting particle aggregation. Furthermore, the modified starch, as a supporting natural polymer chain segment, can crosslink with organic polymers in the modification solution and metal cations in the inorganic acid leaching solution to form a three-dimensional multi-point complex structure, enhancing the stability and spatial network strength of the flocculant. Moreover, the modified starch retains the flexibility of the polymer chain in the starch molecular skeleton, improving the dispersibility and adsorption range of the flocculant, enabling it to act widely on pollutant particles of different sizes. Detailed Implementation
[0046] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] The volcanic rock powder used in this invention was purchased from Lingshou County Shunyong Mineral Products Co., Ltd., with a particle size of 325 mesh and a density of 2.406 g / cm³. 3 ;
[0048] The corn starch used in this invention was purchased from Sichuan Hongjianxin Technology Co., Ltd., and has a density of 3.5 g / cm³. 3 The implementation standard is the national standard.
[0049] Example 1
[0050] This embodiment provides a method for preparing an acid leaching solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0051] Step I: Preparation of pretreated volcanic rock powder
[0052] Volcanic rock powder was placed in a muffle furnace and heated to 300°C for the first time at a heating rate of 15°C / min. After holding at this temperature for 15 min, it was heated to 500°C for the second time at a heating rate of 12°C / min. After holding at this temperature for 35 min, it was heated to 700°C for the third time at a heating rate of 10°C / min. After holding at this temperature for 40 min, it was allowed to cool naturally to room temperature, ground, and passed through a 200-mesh sieve to obtain pretreated volcanic rock powder.
[0053] Step II: Preparation of acid leaching solution
[0054] Weigh out 1500 mL of deionized water, 500 mL of hydrochloric acid and 40 g of oxalic acid and place them in a reaction vessel. Stir the reaction vessel and heat it to 85°C to obtain a mixed acid solution.
[0055] Weigh 150g of pretreated volcanic rock powder and place it in a reaction vessel. Slowly add 1500mL of mixed acid solution. Heat the reaction vessel to 85℃ and keep it at that temperature for 1 hour. After the reaction is complete, wait for the reaction system to cool to room temperature and stand for 6 hours before separating the liquids. The supernatant obtained is the acid leaching solution.
[0056] Example 2
[0057] This embodiment provides a method for preparing an acid leaching solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0058] Step I: Preparation of pretreated volcanic rock powder
[0059] Volcanic rock powder was placed in a muffle furnace and heated to 300°C for the first time at a heating rate of 15°C / min. After holding at this temperature for 20 min, it was heated to 500°C for the second time at a heating rate of 12°C / min. After holding at this temperature for 40 min, it was heated to 700°C for the third time at a heating rate of 10°C / min. After holding at this temperature for 50 min, it was allowed to cool naturally to room temperature, ground, and passed through a 200-mesh sieve to obtain pretreated volcanic rock powder.
[0060] Step II: Preparation of acid leaching solution
[0061] Weigh out 1750 mL of deionized water, 550 mL of hydrochloric acid and 50 g of oxalic acid and place them in a reaction vessel. Stir the reaction vessel and heat it to 90°C to obtain a mixed acid solution.
[0062] Weigh 175g of pretreated volcanic rock powder and place it in a reaction vessel. Slowly add 1750mL of mixed acid solution. Heat the reaction vessel to 90℃ and keep it at that temperature for 1.5h. After the reaction is complete, wait for the reaction system to cool to room temperature and stand for 8h before separating the liquids. The supernatant obtained is the acid leaching solution.
[0063] Example 3
[0064] This embodiment provides a method for preparing an acid leaching solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0065] Step I: Preparation of pretreated volcanic rock powder
[0066] Volcanic rock powder was placed in a muffle furnace and heated to 300°C for the first time at a heating rate of 15°C / min. After holding at this temperature for 25 min, it was heated to 500°C for the second time at a heating rate of 12°C / min. After holding at this temperature for 45 min, it was heated to 700°C for the third time at a heating rate of 10°C / min. After holding at this temperature for 60 min, it was allowed to cool naturally to room temperature, ground, and passed through a 200-mesh sieve to obtain pretreated volcanic rock powder.
[0067] Step II: Preparation of acid leaching solution
[0068] Weigh out 2000 mL of deionized water, 600 mL of hydrochloric acid and 60 g of oxalic acid and place them in a reaction vessel. Stir the reaction vessel and heat it to 95°C to obtain a mixed acid solution.
[0069] Weigh 200g of pretreated volcanic rock powder and place it in a reaction vessel. Slowly add 2000mL of mixed acid solution. Heat the reaction vessel to 95℃ and keep it at that temperature for 2 hours. After the reaction is complete, wait for the reaction system to cool to room temperature and stand for 10 hours before separating the liquids. The supernatant obtained is the acid leaching solution.
[0070] Example 4
[0071] This embodiment provides a method for preparing modified starch for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0072] Step ①: Prepare gelatinized starch
[0073] Weigh out 50g of corn starch and 300mL of deionized water and place them in a reaction vessel. Heat the reaction vessel to 80℃ and keep it at that temperature for 20min. Then cool it to obtain gelatinized starch.
[0074] Step 2: Preparation of modified starch
[0075] Weigh 50g of gelatinized starch and place it in a reaction vessel. Stir the reaction vessel and heat it to 45℃. Add 150mL of 2mol / L sodium hydroxide aqueous solution and stir for 10min. Add 500mL of 50wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and heat the reaction vessel to 65℃. Keep the reaction vessel at this temperature for 2h. After the reaction is complete, wait for the reaction system to cool down and add 1mol / L hydrochloric acid aqueous solution to adjust the pH of the system to 6.5. Filter the system and wash the filter cake twice with deionized water. Transfer the filter cake to an oven at 50℃ and dry it to constant weight. Grind the cake and pass it through a 200-mesh sieve to obtain modified starch.
[0076] Example 5
[0077] This embodiment provides a method for preparing modified starch for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0078] Step ①: Prepare gelatinized starch
[0079] Weigh out 75g of corn starch and 400mL of deionized water and place them in a reaction vessel. Heat the reaction vessel to 85℃ and keep it at that temperature for 30min. Then cool it to obtain gelatinized starch.
[0080] Step 2: Preparation of modified starch
[0081] Weigh 75g of gelatinized starch and place it in a reaction vessel. Stir the reaction vessel and heat it to 50℃. Add 175mL of 2.5mol / L sodium hydroxide aqueous solution and stir for 12min. Add 600mL of 55wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and heat the reaction vessel to 70℃. Keep the reaction vessel at this temperature for 3h. After the reaction is complete, wait for the reaction system to cool down and add 1.5mol / L hydrochloric acid aqueous solution to adjust the pH of the system to 7. Filter the system and wash the filter cake three times with deionized water. Transfer the filter cake to an oven at 55℃ and dry it to constant weight. Grind the cake and pass it through a 200-mesh sieve to obtain modified starch.
[0082] Example 6
[0083] This embodiment provides a method for preparing modified starch for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0084] Step ①: Prepare gelatinized starch
[0085] Weigh out 100g of corn starch and 500mL of deionized water and place them in a reaction vessel. Heat the reaction vessel to 90℃ and keep it at that temperature for 40min. Then cool it to obtain gelatinized starch.
[0086] Step 2: Preparation of modified starch
[0087] Weigh 100g of gelatinized starch and place it in a reaction vessel. Stir the reaction vessel and heat it to 55℃. Add 200mL of 3mol / L sodium hydroxide aqueous solution and stir for 15min. Add 700mL of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and heat the reaction vessel to 75℃. Keep the reaction vessel at this temperature for 4h. After the reaction is complete, wait for the reaction system to cool down and add 2mol / L hydrochloric acid aqueous solution to adjust the pH of the system to 7. Filter the mixture and wash the filter cake 4 times with deionized water. Transfer the cake to an oven at 60℃ and dry it to constant weight. Grind the cake and pass it through a 200-mesh sieve to obtain modified starch.
[0088] Example 7
[0089] This embodiment provides a method for preparing a citric acid complexing solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0090] Step (1) Preparation of precursor solution
[0091] Weigh 150g of citric acid monohydrate and 1000mL of deionized water and place them in a reaction vessel and stir. Add 350g of ferric nitrate nonahydrate and stir for 5 minutes. Add 0.05mol / L sodium acetate aqueous solution to adjust the pH of the system to 4. Heat the reaction vessel to 55℃ and keep it at that temperature for 0.5h to obtain the precursor solution.
[0092] Step 2: Preparation of citric acid complex solution
[0093] Weigh 1200 mL of the precursor solution and place it in a reaction vessel. Stir and slowly add 60 g of 2-hydroxyethylamine. Add saturated ammonium bicarbonate aqueous solution to adjust the pH of the system to 5.5. Heat the reaction vessel to 45°C and keep it at that temperature for 1 h to obtain the citric acid complex solution.
[0094] Example 8
[0095] This embodiment provides a method for preparing a citric acid complexing solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0096] Step (1) Preparation of precursor solution
[0097] Weigh 175g of citric acid monohydrate and 1250mL of deionized water and place them in a reaction vessel and stir. Add 375g of ferric nitrate nonahydrate and stir for 10min. Add 0.07mol / L sodium acetate aqueous solution to adjust the pH of the system to 4.2. Heat the reaction vessel to 60℃ and keep it at this temperature for 1h to obtain the precursor solution.
[0098] Step 2: Preparation of citric acid complex solution
[0099] Weigh 1350 mL of the precursor solution and place it in a reaction vessel. Stir and slowly add 60 g of 2-hydroxyethylamine. Add saturated ammonium bicarbonate aqueous solution to adjust the pH of the system to 5.7. Heat the reaction vessel to 50 °C and keep it at that temperature for 1.5 h to obtain the citric acid complex solution.
[0100] Example 9
[0101] This embodiment provides a method for preparing a citric acid complexing solution for a composite flocculant based on high-efficiency water treatment, including the following steps:
[0102] Step (1) Preparation of precursor solution
[0103] Weigh 200g of citric acid monohydrate and 1500mL of deionized water and place them in a reaction vessel and stir. Add 400g of ferric nitrate nonahydrate and stir for 5-15 minutes. Add 0.10mol / L sodium acetate aqueous solution to adjust the pH of the system to 4.5. Heat the reaction vessel to 65℃ and keep it at this temperature for 1 hour to obtain the precursor solution.
[0104] Step 2: Preparation of citric acid complex solution
[0105] Weigh 1500 mL of the precursor solution and place it in a reaction vessel. Stir and slowly add 60 g of 2-hydroxyethylamine. Add saturated ammonium bicarbonate aqueous solution to adjust the pH of the system to 6.0. Heat the reaction vessel to 55°C and keep it at that temperature for 2 h to obtain the citric acid complex solution.
[0106] Example 10
[0107] This embodiment provides a method for preparing a composite flocculant based on high-efficiency water treatment, including the following steps:
[0108] Step (a) Preparation of mixed monomers
[0109] Weigh out 40g of acrylamide, 20g of diallyl dimethyl ammonium chloride, 10g of 2-hydroxypropyl methacrylate and 500mL of deionized water and place them in a reaction vessel. Mix them evenly to obtain a mixed monomer.
[0110] Step (b): Preparation of modified liquid
[0111] Weigh out 800 mL of deionized water and 5 g of sodium dodecyl sulfate and place them in a reaction vessel under nitrogen atmosphere protection. Stir the mixture and slowly add 800 mL of mixed monomers. Heat the reaction vessel to 55°C and keep it at that temperature for 15 min. Add 20 mL of 50 wt% ammonium persulfate aqueous solution and keep it at that temperature for 4 h to obtain the modified solution.
[0112] Step (c) Preparation of composite flocculant
[0113] Weigh 100 mL of the acid leaching solution prepared in Example 1 and place it in a reaction vessel and stir. Add 20 mL of the modified solution and 10 g of the modified starch prepared in Example 4, stir for 5 min, add 100 mL of the citric acid complex solution prepared in Example 7, heat the reaction vessel to 55 °C, add 1 mol / L sodium hydroxide aqueous solution to bring the pH of the system to 6.5, keep the temperature and react for 15 min. After the reaction is completed, wait for the reaction system to cool to room temperature and stand for 10 h. Transfer the product to a rotary evaporator at 90 °C and evaporate under reduced pressure for 0.5 h. Remove undissolved matter through an 80-mesh sieve to obtain the composite flocculant.
[0114] Example 11
[0115] This embodiment provides a method for preparing a composite flocculant based on high-efficiency water treatment, including the following steps:
[0116] Step (a) Preparation of mixed monomers
[0117] Weigh out 50g of acrylamide, 30g of diallyl dimethyl ammonium chloride, 15g of 2-hydroxypropyl methacrylate and 600mL of deionized water and place them in a reaction vessel. Mix them evenly to obtain a mixed monomer.
[0118] Step (b): Preparation of modified liquid
[0119] Weigh 1000 mL of deionized water and 7 g of sodium dodecyl sulfate and place them in a reaction vessel under nitrogen atmosphere protection. Stir the mixture and slowly add 900 mL of mixed monomers. Heat the reaction vessel to 60°C and keep it at that temperature for 20 min. Add 30 mL of 50 wt% ammonium persulfate aqueous solution and keep it at that temperature for 5 h to obtain the modified solution.
[0120] Step (c) Preparation of composite flocculant
[0121] Weigh 110 mL of the acid leaching solution prepared in Example 2 and place it in a reaction vessel and stir. Add 30 mL of the modified solution and 15 g of the modified starch prepared in Example 5, stir for 7 min, add 110 mL of the citric acid complex solution prepared in Example 8, heat the reaction vessel to 60 °C, add 1.5 mol / L sodium hydroxide aqueous solution to bring the pH of the system to 6.7, keep the reaction at this temperature for 20 min, after the reaction is complete, wait for the reaction system to cool to room temperature and stand for 11 h, transfer the product to a rotary evaporator at 95 °C, evaporate under reduced pressure for 1 h, remove undissolved matter through an 80 mesh sieve to obtain the composite flocculant.
[0122] Example 12
[0123] This embodiment provides a method for preparing a composite flocculant based on high-efficiency water treatment, including the following steps:
[0124] Step (a) Preparation of mixed monomers
[0125] Weigh out 60g of acrylamide, 40g of diallyl dimethyl ammonium chloride, 20g of 2-hydroxypropyl methacrylate, and 700mL of deionized water and place them in a reaction vessel. Mix them thoroughly to obtain a mixed monomer.
[0126] Step (b): Preparation of modified liquid
[0127] Weigh 1200 mL of deionized water and 10 g of sodium dodecyl sulfate and place them in a reaction vessel under nitrogen atmosphere protection. Stir the mixture and slowly add 1000 mL of mixed monomers. Heat the reaction vessel to 65°C and keep it at that temperature for 30 min. Add 40 mL of 50 wt% ammonium persulfate aqueous solution and keep it at that temperature for 6 h to obtain the modified solution.
[0128] Step (c) Preparation of composite flocculant
[0129] Weigh 120 mL of the acid leaching solution prepared in Example 3 and place it in a reaction vessel and stir. Add 40 mL of the modified solution and 20 g of the modified starch prepared in Example 6 and stir for 10 min. Add 120 mL of the citric acid complex solution prepared in Example 9. Heat the reaction vessel to 65 °C and add 2 mol / L sodium hydroxide aqueous solution to bring the pH of the system to 7.0. Keep the reaction at this temperature for 30 min. After the reaction is complete, let the reaction system cool to room temperature and stand for 12 h. Transfer the product to a rotary evaporator at 100 °C and evaporate under reduced pressure for 1 h. Remove undissolved matter through an 80-mesh sieve to obtain the composite flocculant.
[0130] Comparative Example 1
[0131] The difference between this comparative example and Example 12 is that, in step II, when preparing the acid leaching solution, an equal amount of volcanic rock powder is used instead of the pretreated volcanic rock powder.
[0132] Comparative Example 2
[0133] The difference between this comparative example and Example 12 is that, in step (b) when preparing the composite flocculant, gelatinized starch is used in an equal amount to replace modified starch.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 12 is that, in step (b) when preparing the composite flocculant, the precursor liquid is used in place of the citric acid complexing liquid in equal amounts.
[0136] Comparative Example 4
[0137] The difference between this comparative example and Example 12 is that the addition of the modified liquid is omitted in step (b) when preparing the composite flocculant.
[0138] Performance testing:
[0139] The turbidity reduction rate and settling time reduction rate of the composite flocculants prepared in Examples 10-12 and Comparative Examples 1-4 were tested in accordance with the standard T / CECS10356-2024 "Flocculants for Wastewater Treatment of Washed Sand and Gravel Aggregates".
[0140] A simulated industrial wastewater was prepared by mixing ferric chloride, aluminum sulfate, copper sulfate pentahydrate, lead nitrate, sodium chloride, and 2 L of drinking water. The simulated industrial wastewater contained Fe... 3+ Concentration of 200 mg / L, Al 3+ Concentration of 50 mg / L, Pb 2+ Concentration of 100 mg / L and Cu 2+ The concentration was 100 mg / L, and the removal rate of various heavy metal ions in simulated industrial wastewater by the composite flocculants prepared in Examples 10-12 and Comparative Examples 1-4 was determined in accordance with the standard GB 18918-2002 "Discharge Standard of Pollutants for Municipal Wastewater Treatment Plants".
[0141] Anionic dyes methyl orange and rhodamine B (RhB) were mixed with deionized water to obtain simulated industrial dye wastewater. The concentrations of methyl orange and rhodamine B in the simulated industrial dye wastewater were 200 mg / L and 200 mg / L respectively. The mixture was shaken in a constant temperature shaker at 25°C for 12 hours. The absorbance of the dye solution was then measured using a UV spectrophotometer to determine the concentrations of the dye solution before and after the mixing. The removal rates of the composite flocculants prepared in Examples 10-12 and Comparative Examples 1-4 for the anionic dyes methyl orange and rhodamine B (RhB) in the simulated industrial dye wastewater were calculated. The specific data are shown in Table 1.
[0142] Table 1 - Performance Test Data for Each Sample
[0143]
[0144] Data Analysis:
[0145] Comparative analysis of the data in Table 1 reveals that the composite flocculant prepared in this invention, compared to the flocculation process without flocculant, exhibits a turbidity reduction rate of 98.7% and a settling time reduction rate of 87.5% during the flocculation process. This also demonstrates its effectiveness in reducing Fe in simulated industrial wastewater. 3+ The removal rate was 97.9%, and Pb... 2+ The removal rate was 95.4%, Cu 2+ The removal rate was 92.3%, and the removal rate of methyl orange in simulated dye industrial wastewater was 95.8%, and the removal rate of rhodamine B was 85.2%, all of which were better than the control group.
[0146] This invention involves reacting citric acid monohydrate with ferric nitrate nonahydrate under mild acidic conditions to form Fe. 3+ A citric acid complex was subsequently introduced, followed by the introduction of 2-hydroxyethylamine to further participate in the complexation. By providing multiple coordination sites between the amino and hydroxyl groups, the stability and reactivity of the complex structure were enhanced. The addition of an ammonium bicarbonate buffer system and adjustment of the pH to 5.5-6.0 further promoted the formation of Fe... 3+ The complexation state transformation results in a stable complex liquid with carboxyl, hydroxyl, and amino groups.
[0147] Multi-stage heat treatment of volcanic rock powder helps remove organic impurities, open the crystal lattice structure, and expose more active sites. Further acid leaching of the pretreated volcanic rock with a mixed acid solution of hydrochloric acid and oxalic acid effectively dissolves the Al. 3+ Fe 3+ Ca 2+ and Mg 2+ An acid leaching solution was obtained by combining active metal ions and colloidal structures containing silicon and aluminum.
[0148] Corn starch is gelatinized by high-temperature hydrothermal treatment, which destroys the original crystalline structure, exposes more hydroxyl functional groups, and enhances hydrophilicity and reactivity. Subsequently, under alkaline conditions, 3-chloro-2-hydroxypropyltrimethylammonium chloride is introduced to carry out an etherification reaction, introducing quaternary ammonium salt cationic groups, giving the starch a permanent positive charge, thus obtaining modified starch. This not only improves the flocculation performance of the composite flocculant, but also enhances its sedimentation performance.
[0149] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a composite flocculant based on high-efficiency water treatment, characterized in that, Includes the following steps: S1. Acrylamide, diallyl dimethyl ammonium chloride, 2-hydroxypropyl methacrylate and deionized water are placed in a reaction vessel and mixed evenly to obtain a mixed monomer. S2. Place deionized water and sodium dodecyl sulfate in a reaction vessel under nitrogen atmosphere and stir. Slowly add the mixed monomers. Heat the reaction vessel to 55-65℃ and keep it at this temperature for 15-30 min. Add ammonium persulfate aqueous solution and keep it at this temperature for 4-6 h to obtain the modified solution. S3. Place the acid leaching solution in a reaction vessel and stir. Add the modified solution and modified starch, stir for 5-10 minutes, add the citric acid complex solution, heat the reaction vessel to 55-65℃, add sodium hydroxide aqueous solution to the system pH=6.5-7.0, keep the temperature for 15-30 minutes, and then process to obtain the composite flocculant.
2. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 1, characterized in that, In step S1, the ratio of acrylamide, diallyl dimethyl ammonium chloride, 2-hydroxypropyl methacrylate, and deionized water is 4-6 g: 2-4 g: 1-2 g: 50-70 mL; in step S2, the ratio of deionized water, sodium dodecyl sulfate, mixed monomers, and ammonium persulfate aqueous solution is 80-120 mL: 0.5-1 g: 80-100 mL: 2-4 mL, and the concentration of the ammonium persulfate aqueous solution is 50 wt%; in step S3, the ratio of acid leaching solution, modified solution, modified starch, and citric acid complexing solution is 10-12 mL: 2-4 mL: 1-2 g: 10-12 mL, and the concentration of the sodium hydroxide aqueous solution is 1-2 mol / L.
3. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 1, characterized in that, The acid leaching solution is prepared by the following steps: A1. Place the volcanic rock powder in a muffle furnace, calcine it at high temperature, and grind it to obtain pretreated volcanic rock powder; A2. Place the pretreated volcanic rock powder in a reactor, slowly add the mixed acid solution at 85-95℃, heat the reactor to 85-95℃, keep the reaction at this temperature for 1-2 hours, and then process it to obtain the acid leaching solution.
4. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 3, characterized in that, In step A2, the ratio of the pretreated volcanic rock powder to the mixed acid solution is 15-20g:150-200mL, and the mixed acid solution is composed of deionized water, hydrochloric acid and oxalic acid in a ratio of 150-200mL:50-60mL:4-6g.
5. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 3, characterized in that, The method for preparing the pretreated volcanic rock powder is as follows: volcanic rock powder is placed in a muffle furnace and heated to 300°C for the first time at a heating rate of 15°C / min. After holding the temperature for 15-25 min, it is heated to 500°C for the second time at a heating rate of 12°C / min. After holding the temperature for 35-45 min, it is heated to 700°C for the third time at a heating rate of 10°C / min. After holding the temperature for 40-60 min, it is naturally cooled to room temperature, ground, and passed through a 200-mesh sieve to obtain the pretreated volcanic rock powder.
6. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 1, characterized in that, The modified starch is prepared by the following steps: B1. Place corn starch and deionized water in a reaction vessel, heat the reaction vessel to 80-90℃, keep the reaction at this temperature for 20-40 minutes, cool, and obtain gelatinized starch. B2. Place the gelatinized starch in a reaction vessel and stir. Heat the reaction vessel to 45-55℃, add sodium hydroxide aqueous solution, keep warm and stir for 10-15 minutes, add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, heat the reaction vessel to 65-75℃, keep warm and react for 2-4 hours, and then process to obtain modified starch.
7. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 6, characterized in that, In step B1, the ratio of corn starch to deionized water is 5-10g:30-50mL; in step B2, the ratio of gelatinized starch, sodium hydroxide aqueous solution, and 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution is 5-10g:15-20mL:50-70mL, the concentration of sodium hydroxide aqueous solution is 2-3mol / L, and the concentration of 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution is 50-60wt%.
8. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 1, characterized in that, The citric acid complex solution was prepared by the following steps: C1. Place citric acid monohydrate and deionized water in a reaction vessel and stir. Add ferric nitrate nonahydrate and stir for 5-15 minutes. Add sodium acetate aqueous solution to adjust the pH of the system to 4-4.
5. Heat the reaction vessel to 55-65℃ and keep the reaction at this temperature for 0.5-1 hour to obtain the precursor solution. C2. Place the precursor solution in a reaction vessel and stir. Slowly add 2-hydroxyethylamine and add saturated ammonium bicarbonate aqueous solution to adjust the pH of the system to 5.5-6.
0. Heat the reaction vessel to 45-55℃ and keep it at this temperature for 1-2 hours to obtain the citric acid complex solution.
9. The method for preparing a composite flocculant based on high-efficiency water treatment according to claim 8, characterized in that, In step C1, the ratio of citric acid monohydrate, deionized water, and ferric nitrate nonahydrate is 15-20g:100-150mL:35-40g, and the concentration of the sodium acetate aqueous solution is 0.05-0.10mol / L; in step C2, the volume ratio of the precursor solution and 2-hydroxyethylamine is 120-150mL:6g.
Citation Information
Cited By
Material treatment method for synchronously recycling acid and iron ions in acid mud
CN121627281A
A material treatment method for simultaneous recovery and utilization of acid and iron ions from acidic sludge.
CN121627281B
